The Impact of Maqashid Syariah Performance on the Profitability of Full-fledged Islamic Banks in Indonesia - Maryam, Siti; Ruhana, Nafisah (Journal of Applied Islamic Economics and Finance, 2025)
Full-fledged Islamic Banks generally show lower profitability compared to conventional banks due to their dual objectives: achieving profit while implementing Islamic principles through maqashid sharia. While this approach may enhance reputation and customer loyalty, it can also incur social costs that reduce earnings. This study examines the effect of maqashid sharia, specifically the dimensions of education, justice, and welfare, on the profitability of Full-fledged Islamic Banks in Indonesia during 2017–2023. Using Return on Assets (ROA) as the profitability indicator, this study applies a quantitative method with panel data regression on 16 banks listed with the Financial Services Authority (OJK). The results indicate that education and welfare have a positive and significant impact on profitability, while justice does not. These findings suggest that strengthening education and social welfare programs can support the financial performance of Islamic banks.